2019
DOI: 10.1097/pas.0000000000001276
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Budding and Other Risk Factors of Lymph Node Metastasis in Submucosal Early Gastric Carcinoma

Abstract: Compared with early gastric intramucosal carcinoma, submucosal carcinoma is known to have a higher risk for lymph node metastasis (LMN), but risk factors in submucosal carcinoma remain elusive. In this multicenter study with 621 radical gastrectomies for submucosal early gastric carcinoma, we investigated tumor budding and other risk factors of LMN that were identified in 172 cases (27.7%). Overall, independent high-risk factors for LMN included lymphovascular invasion (odds ratio, 3.9; 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
0
21
2
Order By: Relevance
“…Our study proved that there were no differences in the aggressive tumor features, such as N stage, M stage, and tumor size between AM and other three histologic subtypes in EGC, which is not consistent with previous researches [9]. We think this is due to the fact that the comparison is not just with adenocarcinoma in the research mentioned above.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Our study proved that there were no differences in the aggressive tumor features, such as N stage, M stage, and tumor size between AM and other three histologic subtypes in EGC, which is not consistent with previous researches [9]. We think this is due to the fact that the comparison is not just with adenocarcinoma in the research mentioned above.…”
Section: Discussioncontrasting
confidence: 92%
“…There were some researches on the prognosis of GC patients with AM [8,9]. However, there is no report on the comparison of prognosis among AM, classic adenocarcinoma (CA), MAC and SRCC in EGC and AGC, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These results were confirmed in a subgroup analysis of intestinal-type cancers but not in diffuse-type adenocarcinoma. 76 In their evaluation of tumour budding in 621 radical gastrectomies for submucosal early gastric carcinoma, 77 Du et al identified high-grade tumour budding as a predictor of lymph node metastases (OR 3.3, 95% CI 1.9–5.9). Moreover, when Ulase et al applied the ITBCC tumour-budding score to 456 surgically resected gastric cancers, they found that the BD score was significantly associated with sex, Laurén phenotype, pT-, pN- and pM classification, as well as perineural invasion and survival times.…”
Section: Clinical Implications Of Tumour Budding In Oesophageal and Gastric Cancermentioning
confidence: 99%
“…Tumor budding (TB) is a well-known risk factor for LNM in early-stage colorectal cancer [ 10 , 11 , 12 , 13 ]. Recently, it has also emerged as a potential predictor of LNM in gastric cancer (GC) [ 12 , 14 , 15 , 16 , 17 , 18 , 19 ]. However, studies on the association between TB and LNM in GC have been conducted mainly in intestinal-type carcinoma [ 12 , 14 , 19 ], as it is difficult to discern TB in poorly cohesive carcinoma (PCC) cases because of its discohesive pattern [ 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%